ANALISIS PERSEPSI KORUPSI PAJAK DAN IKLIM ORGANISASI TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI KARYAWAN - Arif Fajar Wibisono; Yudha Catur Kusuma N. (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2017)
This study aims to determine whether perceptions of corruption and organizational climate affect the compliance of personal taxpayers. This explanatory study used quantitative approach of statistical parametric test and multiple linear regressions with questionnaire instrument. This study involved personal taxpayer in the area of KPP Pratama Kota Surakarta. The result of this study confirms that the perceptions of individual tax corruption and organizational climate affect the compliance of personal taxpayers. The better the organization’s climate in emphasizing tax compliance is, the higher the level of compliance personal taxpayers is. In addition, the higher the level of perception of a person’s corruption of the tax apparatus is severely punished then increasing the compliance of personal taxpayers’ increases.